The MHC in bovine theileriosis - Morrison, W. Ivan; Goddeeris, Bruno M.; Teale, A.J. (1988)
This paper presents a summary of the current knowledge on the MHC restriction of Theileria specific cytotoxic T cell responses and indicated how MHC phenotype may influence the parasite strain specificity of the response. The data presented were derived from studies of the response in vivo as well as of cytotoxic T cell lines and clones established in vitro from immune cattle. Two antigenically different stocks of the parasite, namely T. parva (Muguga) and T. parva (Marikebuni), were used. Animals immunized with T. parva (Marikebuni) are protected against challenge with T. parva (Muguga), wheras a proportion of animals immunized with T. parva (Muguga) are susceptible to challenge with T. parva (Marikebuni). The results indicate that there is a hierarchy dominance among BoLA class I molecules in the restriction of the Theileria - specific cytotoxic T cell response.